We have that the equation is as follows:
To solve this equation, we can proceed as follows:
1. Add the like terms in the radicand (-2 + 8 = 6):
2. Square both sides of the equation:
3. We already know that the square root of a number is like raising that number to the fraction 1/2. Then, we have - using the power to a power rule:
4. Therefore, we have:
5. If we subtract x and 6 from both sides of the equation, we have:
6. Now, we have a second-degree (quadratic) polynomial that we can solve by factoring or by using the quadratic formula:
7. We can factor this polynomial if we find two numbers:
• a*b = -6
,
• a + b = -1
Then, both numbers are:
• a = 2
,
• b = -3
,
• a*b = 2 * -3 = -6
,
• a + b = 2 -3 = -1
Then, the above polynomial can be factored as follows:
8. The solutions for this equation are:
9. Now, to check these two solutions, we need to substitute these values into the original equation as follows:
For x = -2
This is an extraneous solution. Although we got x = -2 as a solution to the resulting equation, it is not really a solution to the original equation. Therefore, x = -2 is an extraneous solution.
For x = 3
Therefore, x = 3 is a solution to the original equation.
In summary, we have that the solution to the original equation:
is x = 3.
There is an extraneous solution, x = -2 (it is not an actual solution to the original equation).